Student Skills in Operating CorelDraw 2020 Application on Class XI DKV SMKN 4 Samarinda - Aisha Syifa Salsabila; Ramaulvi Muhammad Akhyar; Galih Yudha Saputra (TEPIAN, 2024)
This research is descriptive qualitative in nature and was conducted during the 2023/2024 academic year on the topic of operating CorelDraw 2020. The subjects of this study were 34 students from class XI DKV 2. The object of the research was the students' skills in operating CorelDraw 2020, categorizing them as very skilled, skilled, or less skilled. The research activities included observation, practical tests, interviews, and documentation. Data analysis techniques involved data reduction, data presentation, and triangulation. Based on the research results and discussions, it can be concluded that the skills of class XI students at SMK Negeri 4 Samarinda in practicing exercises related to operating CorelDraw 2020 are generally skilled. Specifically, it was found that 11 students were very skilled, 13 students were skilled, and 10 students were less skilled in operating CorelDraw 2020. Factors contributing to the less skilled performance of some students include a lack of active participation in lessons, not following the teacher's demonstration steps, and not actively asking questions or taking notes on the material. On the other hand, the factors contributing to the skilled performance of students include regularly reviewing lesson materials at home and using tutorial videos for learning. Generally, students struggled with tasks such as managing outlines, combining objects, inserting objects using PowerClip Inside, positioning objects with shortcuts, using the Artistic Media tool, trimming objects using other objects, and using LiveSketch.